Freedom flyers : the Tuskegee Airmen of World War II - Moye, J. Todd (Oxford University Press, 2010)
Prologue: This is where you sit -- The use of Negro manpower in war -- The Black Eagles take flight -- The experiment -- Combat on several fronts -- The trials of the 477th -- Integrating the Air Force -- Epilogue: Let's make it a holy crusade all around